INVESTMENT IN REAL ESTATE PRAGUE CASE STUDY - Cheremnykh, Anna (2013)
This paper analyzes the influence of several factors on rental and purchase price of Real Estate in Prague. The idea is that purchase and rental price could be influenced by different factors. To make a decision about "buy to rent" investment it is necessary to consider both sides. The aim is to conduct thorough analysis to find out whether differential factors exist, and if so, what they are. The comparison of these factors and their separated effects helps to understand the total effect on potential profitability and to make right decision about attractive properties for "buy to rent" investment. The paper serves to inform investors who are making decisions about investment properties.